Long‐term outcome of Miniature Schnauzers with genetically confirmed demyelinating polyneuropathy: 12 cases. (1st August 2020) - Farré Mariné, Alba; Granger, Nicolas; Bertolani, Coralie; Mascort Boixeda, Joan; Shelton, G. Diane; Luján Feliu‐Pascual, Alejandro
Abstract: Background: A demyelinating polyneuropathy with focally folded myelin sheaths was reported in 3 Miniature Schnauzers in France in 2008 and was predicted to represent a naturally occurring canine homologue of Charcot‐Marie‐Tooth (CMT) disease. A genetic variant of MTRM13/SBF2 has been identified as causative in affected Miniature Schnauzers with this polyneuropathy. Objective: To provide data on the long‐term progression in affected Miniature Schnauzers from Spain confirmed with the MTRM13/SBF2 genetic variant. Animals: Twelve Miniature Schnauzers presented between March 2013 and June 2019. Methods: Only dogs presented with consistent clinical signs and homozygous for the MTRM13/SBF2 genetic variant were included. Clinical signs, age of onset and presentation, time from onset to presentation, treatment, outcome, and time from diagnosis to final follow‐up were retrospectively reviewed. Results: The hallmark clinical signs at the time of presentation were regurgitation with radiologically confirmed megaesophagus (11/12) and aphonic bark (11/12) with or without obvious neuromuscular weakness despite electrodiagnostic evidence of appendicular demyelinating polyneuropathy. Age of onset and clinical presentation were 3‐18 and 4‐96 months, respectively. Treatment was mostly symptomatic and consisted of head elevation during meals, antacids, prokinetics, bethanechol, sildenafil, mirtazapine, or some combination of these. During the follow‐up period (7‐73 months), clinical signs were unchanged in (11/12) cases with aspiration pneumonia developing occasionally (6/12) and being the cause of death in 1 dog. Conclusions and Clinical Importance: Demyelinating polyneuropathy of Miniature Schnauzers tends to remain stable over the long term leading to a good prognosis with preventive feeding measures and symptomatic treatment to control aspiration pneumonia.